(untitled) - Tran, Thi Kim Thi (Can Tho, 2014)
Aimed to examine the effects of content-schemata activating activities on pre-reading stage and to obtain insights into learners' attitudes towards the activities used int he study
Keywords: Ngôn ngữ Anh,English language; Dạy và học,Study and teaching